Gemcitabine as adjuvant chemotherapy in patients with high-risk early breast cancer—results from the randomized phase III SUCCESS-A trial - de Gregorio, Amelie; Häberle, Lothar; Fasching, Peter; Müller, Volkmar; Schrader, Iris; Lorenz, Ralf; Forstbauer, Helmut; Friedl, Thomas W.P.; Bauer, Emanuel; de Gregorio, Nikolaus; Deniz, Miriam; Fink, Visnja; et al. (Breast Cancer Research, 2020)
Background: When chemotherapy is indicated in patients with early breast cancer, regimens that contain anthracyclines and taxanes are established standard treatments. Gemcitabine has shown promising effects on the response and prognosis in patients with metastatic breast cancer. The SUCCESS-A trial (NCT02181101) examined the addition of gemcitabine to a standard chemotherapy regimen in high-risk early breast cancer patients. Methods: A total of 3754 patients with at least one of the following characteristics were randomly assigned to one of the two treatment arms: nodal positivity, tumor grade 3, age ≤ 35 years, tumor larger than 2 cm, or negative hormone receptor status. The treatment arms received either three cycles of 5-fluorouracil, epirubicin, and cyclophosphamide, followed by three cycles of docetaxel (FEC → Doc); or three cycles of FEC followed by three cycles of docetaxel and gemcitabine (FEC → Doc/Gem). The primary study aim was disease-free survival (DFS), and the main secondary objectives were overall survival (OS) and safety. Results: No differences were observed in the 5-year DFS or OS between FEC → Doc and FEC → Doc/Gem. The hazard ratio was 0.93 (95% CI, 0.78 to 1.12; P = 0.47) for DFS and 0.94 (95% CI, 0.74 to 1.19; P = 0.60) for OS. For patients treated with FEC → Doc and FEC → Doc/Gem, the 5-year probabilities of DFS were 86.6% and 87.2%, and the 5-year probabilities of OS were 92.8% and 92.5%, respectively. Conclusion: Adding gemcitabine to a standard chemotherapy does not improve the outcomes in patients with high-risk early breast cancer and should therefore not be included in the adjuvant treatment setting. Trial registration: Clinicaltrials.gov NCT02181101 and EU Clinical Trials Register EudraCT 2005-000490-21. Registered September 2005.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Chemotherapy; Early breast cancer; Gemcitabine